Design and Evaluation of a Web-Based Interactive System for Child Growth Monitoring and Cognitive Development - Muhammad Hasanuddin; Abil Alwi Prayoga (CV. Raskha Media Group, 2026)
Continuous monitoring of child growth and development is critical to ensuring optimal health outcomes and early cognitive development; however, real-world practices are often constrained by limited access to information, time barriers, and low parental engagement. This study proposes and evaluates a web-based interactive system that integrates child growth monitoring with cognitive learning media into a unified digital platform. The research adopts a user-centered design approach, followed by system development using web technologies (PHP) and interactive multimedia (ActionScript), and comprehensive evaluation through functional testing and user studies. The proposed system incorporates key functionalities, including nutritional status assessment, age-based ideal body weight estimation, interactive learning modules for early childhood, and access to health information and primary healthcare services. Evaluation results demonstrate robust system performance, with all features operating reliably across multiple browser environments and producing outputs consistent with established manual calculations. Furthermore, user study findings indicate high acceptance levels and improved parental engagement in monitoring and supporting child development. Conceptually, this work contributes to bridging digital health and educational technology through an integrated web-based multimedia approach. In practice, the system offers a scalable solution to enhance preventive healthcare services and early cognitive stimulation, particularly in underserved communities with limited access to conventional healthcare infrastructure.